Ruralno društvo i ruralna geografija u prošlosti i budućnosti - Todorović Marina (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
Through out history rural society has progressed from primitive village community to modern, developed rural society. Until the first half of XX century farmers were the largest and most important category in European society. Various geographical, climatic, economical, cultural, historical and other factors have made difference in rural societies in Europe and in Serbia it’s self. In the second half of XX century the role of rural society has significantly changed in social, political and economic system, which had big impact on development of villages and agriculture. In second part of this paper author considers relationships and changes of rural society with various ways of rural geography development. Rural geography rationally explains new premises of rural society with complete society processes and practical problems (reorganization of village communities, changes in their traditional agricultural structure, local community organizations and ethno culture) in the spot light of new rural paradigm - complementarily development. Therefore, the main interest of rural geographers is attractiveness of rural space. Second strong influence in rural geography development is creation of new technological methods, which enable more detailed and complexed geographical researches and has great applicative importance.